TAREKAT DAN INTELEKTUALITAS: Studi Keterlibatan Kalangan Intelektual dalam Tarekat Tijaniyah di Kota Banjarmasin - ., Saifuddin; ., Wardani; Nirwana, Dzikri (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
The development of tariqat in Indonesia is historically and sociologically related to the climate and culture of the people who in the past was formed by rural culture. However, in recent developments, in South Kalimantan for example, the assumption is very different. Although, this tariqat is usually described as traditional, backward, and associated with the countryside, it is not entirely true. With its tradisional nature, the tariqat become attractions for scholars. Those with rational thingkings entering this world with diverse motivations. There are two complementary sides. On the one hand, rational intellectuals/scholars enter into the tariqat and give a new baseline. On the other hand, the members of the tariqat also renew themselves. Motivations that drive the interest to this tariqat are doctrinal, rational, moral, and psychological. This motivation does not stand alone; it is intertwined and supports each other, in the internalization of the tariqat into the consciousness of the individual.